MALL: The pedagogical challenges - Burston, Jack (My University, 2014)
In this paper the development of mobile-assisted language learning (MALL) over the past 20 years is reviewed with a particular focus on the pedagogical challenges facing its exploitation. Following a consideration of the definition of mobile learning, the paper describes the dominant mobile technologies upon which MALL applications have been based: MP3 players, personal digital assistants, and mobile phones. It then identifies the prevalent methodological approach that has underlain the great majority of MALL implementations: a behaviorist, teacher-centered, transmission model of instruction. However, though rarely implemented, MALL is equally capable of supporting more innovative constructivist, collaborative, learner-centered instruction, examples of which are examined. Besides being restricted by a pedagogical approach very much out of step with methodologies that have guided foreign language teaching for nearly four decades, MALL has also been constrained by access to technology. In part, this problem has been due to the necessity of acquiring mobile devices for student usage and the costs associated with mobile network and Internet connections. Even more so, the exploitation of mobile devices for language learning has been hampered by a lack of hardware standardization and entrenched operating system incompatibilities. The paper concludes that MALL has yet to realize its full potential and that achieving this aim is more a matter of pedagogy than technology. The financial and technological factors that have impeded the effective exploitation of MALL are likely to be resolved as operating system incompatibilities are overcome by market forces and students as well as teachers acquire suitable mobile devices for their own personal use. The future of MALL lies in the exploitation of the communication and multimedia affordances of mobile devices in ways that support collaborative, task-based learning both within and outside of the classroom. © 2014 Taylor & Francis.
Keywords: Foreign language instructional technology; Learning theories; Mobile communication; Mobile phones; Mobile-assisted language learning